ADMINISTRATIVE SYSTEMS ON SAVING AND LOAN DATA PROCESSING KUD BINA WARGA MUKTI - Eva Susanti; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2001)
KUD has three business units, one of whom is a business unit pinjam.tujuan save this business unit is to develop members' income in the form of deposits. of these deposits can be lent again to members in need. in order to avoid the trap of moneylenders. but still a lot of members who are less aware of and heed the rules that have been established, so much happened in arrears, arrears which is a constraint for this unit. System has been applied to the savings and loan units are no longer effective. to overcome existing constraints, these systems need to be reviewed. changes in the system that has been used, expected to be able to overcome all the obstacles.